Memanfaatkan Serat Tali Dari Daun Lidah Mertua Dan Botol Plastik Menjadi Kerajinan Keranjang Air Mineral - Yadi, Supri; Saputra, Pio Rahmat; Saputra, Indra Lesmana; Septiawan, Agus; Syaputra, Kevin; Prasetya, Andwini; Nur’aini, Hesti; Fariadi, Herri (LPPM Universitas Dehasen Bengkulu, 2025)
Waste management sometimes does not get serious attention, awareness of the importance of the environment is still low, so that environmental pollution begins to occur and has a bad impact on the surrounding environment. Utilization and processing are adjusted to the type of waste. Inorganic waste can be recycled into craft products that can be used such as plastic bottles. The KKN-T community service program is carried out by providing education through socialization of waste sorting and training activities for making crafts from snake tongue fiber and used plastic bottles. Sorting 3R waste to residents of RT.41, especially inorganic waste, namely plastic bottles, jars and cardboard by direct exposure, providing information from leaflets, as well as information on its economic value. Furthermore, conducting training in processing inorganic waste into crafts in the form of mineral water baskets. Utilization of snake tongue fiber and plastic bottles into mineral water basket crafts can be an alternative for processing inorganic waste that has economic value and is environmentally friendly. This community service can be an inspiration for residents of RT.41 to develop other craft products that utilize natural materials and inorganic waste. In addition, the high economic value of the craft products produced requires further action that can increase public awareness in implementing the 3R principle.